Cocoa Polyphenols: Can We Consider Cocoa and Chocolate as Potential Functional Food? - Djurdjica Ackar; Kristina Valek Lendić; Marina Valek; Drago Šubarić; Borislav Miličević; Jurislav Babić; Ilija Nedić (Journal of Chemistry)
Chocolate has been consumed as confection, aphrodisiac, and folk medicine for many years before science proved its potential health benefiting effects. Main compounds of cocoa and chocolate which contribute to human health are polyphenols that act as antioxidants and have potential anti-inflammatory, cardioprotective, antihepatotoxic, antibacterial, antiviral, antiallergenic, and anticarcinogenic properties. This paper gives a short overview of scientific literature regarding cocoa polyphenols and influence of cocoa and chocolate on human health. Although research on health benefits of dark chocolate and cocoa is quite extensive nowadays and shows potentially beneficial effects of dark chocolate and cocoa, there are still lots of unknowns and some controversies. This is obviously an area that needs more research in order to determine factual influence of chocolate on health.